Simulation of a hydrogen hybrid battery-fuel cell vehicle (2015)
This paper describes a vehicle simulation toolbox developed under Matlab® environment, which can be used to estimate the range of a vehicle battery, or a fuel cell/battery hybrid system. The model is function of mechanical and physical variables that depend not only on the vehicle but also on the ground. This toolbox can be extended to GPS tracking files by means of reading data file plug-ins. Even standard drive cycles can be simulated. Battery and hydrogen consumption, hydrogen storage tank level, battery state of charge, power consumption and fuel cell energy production, maximum range and maximum number of cycles for a real route can be determined. The model facilitates the prediction of the vehicle range and the hydrogen and energy consumption. Real route simulation gives a good approximation of the vehicle speed close to real-life services instead of using driving cycles that are quite arbitrary approximations to a real route.